N and P Co-doped Green Waste Derived Hierarchical Porous Carbon as a Supercapacitor Electrode for Energy Storage: Electrolyte Effects - Rabbani, Muhammad Asif; Oladipo, Akeem Adeyemi; Kusaf, Mehmet (Wiley-V C H Verlag Gmbh, 2023)
N, P dual-doped watermelon peel-derived carbon (NPW) was prepared and found to exhibit a larger specific surface area of 1809 m(2) g(-1) and improved hierarchically interconnected pores than N-doped and P-doped carbons. The NPW electrode exhibits excellent electrochemical activity in a three-electrode setup with 1 M H2SO4, 6 M KOH, and 1 M Na2SO4 electrolytes; with high specific capacitance (498.8, 397.6, and 378.6 F g(-1) at 1 A g(-1), respectively) and an average capacitance retention of similar to 96.9 % after 10,000 charge-discharge cycles at 10 A g(-1). The NPW//NPW-based symmetric cell with 1 M H2SO4-PVA-electrolyte provided a high energy density of 71.84 Wh kg(-1) at 1 A g(-1) and a specific capacitance of 263.9 F g(-1). In the neutral electrolyte, NPW showed a wider operating voltage window of up to 2.0 V with no discernible anodic current and delivered 97.11 Wh kg(-1) energy density.
Keywords: Biowastes; clean energy storage; EDLC electrode materials; doped carbon; supercapacitor